Identification of Pathogenic Bacteria in Tofu Water and Sugarcane Water in Pontianak City - Hermantika, David Deovia Triputra; Ihsan, Bagus Muhammad; Kamilla, Laila; Khayan, Khayan; Hanif, Muhammad Ifham (Poltekkes Kemenkes Palu, 2024)
Tofu water and sugar cane juice are trendy drinks, especially in Pontianak City. Pathogenic bacterial contamination in tofu water and sugar cane juice can be a severe threat if the immune system is weak. This research aims to identify pathogenic bacteria in Pontianak City tofu water and sugar cane water. The methods used are culture methods and biochemical tests. The research samples were tofu water and sugar cane juice sold in the community. The sample was selected using a purposive sampling technique. In this study, the bacteria found in the identification of bacteria in tofu water and sugar cane water were Klebsiella pneumoniae, Shigella dysenteriae, Staphylococcus aureus, Enterobacter aerogenes, Salmonella typhi, and Escherichia coli. Bacteria dominate, while in sugarcane juice, it is dominated by Escherichia coli, followed by Klebsiella pneumoniae. The research results can also be the basis for better policies and preventive measures related to the safety of the quality of tofu water and sugar cane juice in Pontianak City. Therefore, this research can be relevant to environmental protection and public health in Pontianak.